2013
DOI: 10.1002/jgrc.20098
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the summer shelf circulation and transient upwelling off Ningaloo Reef, Western Australia

Abstract: [1] The shelf circulation off Ningaloo Reef near the North West Cape of Western Australia is driven by complex interactions between the southward flowing Leeuwin Current and wind-driven currents that episodically reverse the coastal flow toward the north. The presence of these northward (equatorward) wind-driven currents is thought to make this section of coast one of the few locations along Western Australia to experience periodic coastal upwelling. We used a combination of field observations and numerical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 63 publications
(103 reference statements)
3
41
0
Order By: Relevance
“…The model formulation and numerical algorithms are described in detail in Shchepetkin and McWilliams (2005), and have been used to simulate the circulation and upwelling processes in a range of ocean basins (e.g. Di Lorenzo et al, 2007;Dong et al, 2009;Haidvogel et al, 2008;Marchesiello et al, 2003;Xu et al, 2013).…”
Section: Roms Configuration and Validationmentioning
confidence: 99%
“…The model formulation and numerical algorithms are described in detail in Shchepetkin and McWilliams (2005), and have been used to simulate the circulation and upwelling processes in a range of ocean basins (e.g. Di Lorenzo et al, 2007;Dong et al, 2009;Haidvogel et al, 2008;Marchesiello et al, 2003;Xu et al, 2013).…”
Section: Roms Configuration and Validationmentioning
confidence: 99%
“…Studies by Hansen et al (2005), Pearce et al (2006), Rennie et al (2009), Rossi et al (2013) and Xu et al (2013) Currents. Pearce et al (2006) expanded on this and provided insight from the first long-term (27 month) field study of physical ocean processes including upwelling off Western Australia.…”
Section: Introductionmentioning
confidence: 98%
“…Rennie et al (2009) studied upwelling near Perth, Western Australia, using the Regional Ocean Model System (ROMS) and found that local sporadic upwelling was driven by a combination of physical processes including wind, mean current flow and eddy activity. A similar approach was used by Xu et al (2013) to study episodes of upwelling near Ningaloo Reef, while Rossi et al (2013) used 15 years of satellite data to quantify upwelling along sections of the west Australian coast. Favourable conditions ranged from a maximum of 140 days near Ningaloo to just a few days per year for locations in the south.…”
Section: Introductionmentioning
confidence: 99%
“…Our results display similar performance to Xu et al . [] and generally captured the dominant hydrodynamic processes operating on the shelf.…”
Section: Resultsmentioning
confidence: 99%
“…An additional characteristic that distinguishes the Ningaloo shelf from most shelves underlying other ECBS is the generally much steeper shelf slope (∼0.02 versus <0.01) [ Lentz and Chapman , ]. The steep slope, combined with seasonally strong stratification, causes upwelled waters to be mainly sourced from the interior water column rather than from the near‐bed region [ Lowe et al ., ; Xu et al ., ], consistent with the theoretical response to the locally high‐slope Burger numbers [see Lentz and Chapman , ]. As a consequence, the shallower source depth of the upwelled water, combined with the oligotrophic composition of the Leeuwin Current source waters, substantially limit the degree to which wind‐driven upwelling events cause temperature depressions and elevated nutrients in coastal waters along the Ningaloo Peninsula [ Koslow et al ., ].…”
Section: Introductionmentioning
confidence: 99%